Final solution to the open problem regarding double stars proposed by MARR and wallis - Afzal H.U. (Utilitas Mathematica, 2022)
In 1970, A. Kotzig and A. Rosa introduced the idea of edge-magic total labeling of graphs. In this article, we will provide the final solution to an open problem, regarding edge-magicness of the double star, 5m,n, originally proposed by A. M. Marr and W. D. Wallis, for all possible values of m and n, hence closing it. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.